Job Search and Frictional Unemployment : Some Empirical Evidence - Bruce, C.; Marshall, J. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1976)
The purpose of this paper is to report on some recent empirical research undertaken in order to provide additional information concerning the frictionally unemployed.